Conservation of Histone Binding and Transcriptional Repressor Functions in a Schizosaccharomyces pombe Tup1p Homolog - Mukai, Yukio (American Society for Microbiology, 1999)
The Ssn6p-Tup1p corepressor complex is important to the regulation of several diverse genes in Saccharomyces cerevisiae and serves as a model for corepressor functions. To investigate the evolutionary conservation of these functions, sequences homologous to the S. cerevisiae TUP1 gene were cloned from Kluyveromyces lactis (TUP1) and Schizosaccharomyces pombe (tup11(+)). Interestingly, while the K. lactis TUP1 gene complemented an S. cerevisiae tup1 null mutation, the S. pombe tup11(+) gene did not, even when expressed under the control of the S. cerevisiae TUP1 promoter. However, an S. pombe Tup11p-LexA fusion protein repressed transcription of a corresponding reporter gene, indicating that this Tup1p homolog has intrinsic repressor activity. Moreover, a chimeric protein containing the amino-terminal Ssn6p-binding domain of S. cerevisiae Tup1p and 544 amino acids from the C-terminal region of S. pombe Tup11p complemented the S. cerevisiae tup1 mutation. The failure of native S. pombe Tup11p to complement loss of Tup1p functions in S. cerevisiae corresponds to an inability to bind to S. cerevisiae Ssn6p in vitro. Disruption of tup11(+) in combination with a disruption of tup12(+), another TUP1 homolog gene in S. pombe, causes a defect in glucose repression of fbp1(+), suggesting that S. pombe Tup1p homologs function as repressors in S. pombe. Furthermore, Tup11p binds specifically to histones H3 and H4 in vitro, indicating that both the repression and histone binding functions of Tup1p-related proteins are conserved across species.